(-2/3) ^ -13 * (-2/3) ^ 8 = (-2/3) ^ (-2x + 1)​

Question

(-2/3) ^ -13 * (-2/3) ^ 8 = (-2/3) ^ (-2x + 1)​

in progress 0
Elliana 2 months 2021-10-10T18:53:55+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-10T18:55:10+00:00

    Answer:

    1^2x-6

    Step-by-step explanation:

    (-2/3)^(-13)×(-2/3)^(8) = (-2/3)^(-2x+1)

    (-2/3)^(-5) = (2/3)^(-2x+1)

    (-2/3)^5×3/(-2)^(-2x+1)

    1^(-5)/1^(-2x+1)

    1^-5+2x-1

    1^-6+2x

    1^2x-6

    0
    2021-10-10T18:55:54+00:00

    Answer:

    x=3

    Step-by-step explanation:

    (-2/3)^-13 * (-2/3)^8 = (-2/3)^(-2x+1)

    since base is same we will add the powers

    (-2/3)^(-13+8) = (-2/3)^(-2x+1)

    (-2/3)^(-5) = (-2/3)^(-2x+1)

    since base is same,

    equating powers

    -5= -2x+1

    -5-1 = -2x

    -6 = -2x

    -6/-2= x

    3= x

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )